Where are we at with short bowel syndrome and small bowel transplant - Yildiz, Baris Dogu (Baishideng Publishing Group Co., Limited, 2012)
Intestinal failure can be defined as the critical reduction of functional gut mass below the minimal amount necessary for adequate digestion and absorption to satisfy body nutrient and fluid requirements in adults or children. Short bowel syndrome (SBS) is characterized by a state of malabsorption following extensive resection of the small bowel. SBS may occur after resection of more than 50% and is certain after resection of more than 70% of the small intestine, or if less than 100 cm of small bowel is left. Several treatment modalities other than total parenteral nutrition, including hormones (recombinant human growth hormone, glucagon-like peptide-2) and tailoring surgeries (Bianchi procedure, serial transverse enteroplasty), had been proposed, however these were either experimental or inefficient. Small bowel transplant is a rather new approach for SBS. The once feared field of solid organ transplantation is nowadays becoming more and more popular, even in developing countries. This is partially secondary to the developments in immunosuppressive strategy. In this regard, alemtuzumab deserves special attention. There are more complex surgeries, such as multivisceral transplantation, for multi-organ involvement including small bowel. This latter technique is relatively new when compared to small bowel transplant, and is performed in certain centers worldwide. In this review, an attempt is made to give an insight into small bowel syndrome, small bowel transplantation, and related issues.